Dealing With Deans and Academic Medical Center Leadership: Advice From Leaders. (6th April 2018) - Sanfilippo, Fred; Powell, Deborah; Folberg, Robert; Tykocinski, Mark
The 2017 Association of Pathology Chairs Annual Meeting included a session for department chairs and other department leaders on "how to deal with deans and academic medical center leadership." The session was focused on discussing ways to foster positive relationships with university, medical school, and health system leaders, and productively address issues and opportunities with them. Presentations and a panel discussion were provided by 4 former pathology chairs who subsequently have served as medical deans and in other leadership positions including university provost, medical center CEO, and health system board chair. There was a strong consensus among the participants on how best to deal with superiors about problems, conflicts, and requests for additional resources and authority. The importance of teamwork and accountability in developing a constructive and collaborative relationship with leaders and peers was discussed in detail. Effectiveness in communication, negotiation, and departmental advocacy were highlighted as important skills. As limited resources and increased regulations have become growing problems for universities and health systems, internal stress and competition have increased. In this rapidly changing environment, advice on how chairs can interact most productively with institutional leaders is becoming increasingly important.